EMOTIONAL FACTOR OF STUDENT LEARNING: CONTENT, STRUCTURE AND SIGNIFICANCE IN SECURITY QUALITIES OF EDUCATION (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the problem of the emotional factor of instruction structure and essence. Author defines the notion emotional factor of instruction establishes the significance of emotional factors at the guaranteeing quality of the modern education.
Keywords: emotional factor of instruction; emotions; motives; structure of motive of personality